The expression, localization and function of α7 nicotinic acetylcholine receptor in rat corpus cavernosum. (24th August 2017) - Faghir-Ghanesefat, Hedyeh; Rahimi, Nastaran; Yarmohammadi, Fatemeh; Mokhtari, Tahmineh; Abdollahi, Ali Reza; Ejtemaei Mehr, Shahram; Dehpour, Ahmad R
Abstract: Objectives: Alpha7 nicotinic acetylcholine receptor (α7-nAChR), an emerging pharmacological target for a variety of medical conditions, is expressed in the most mammalian tissues with different effects. So, this study was designed to investigate the expression, localization and effect of α7-nAChR in rat corpus cavernosum (CC). Methods & Key findings: Reverse transcription polymerase chain reaction (RT-PCR) revealed that α7-nAChR was expressed in rat CC and double immunofluorescence studies demonstrated the presence of α7-nAChR in corporal neurons. The rat CC segments were mounted in organ bath chambers and contracted with phenylephrine (0.1 μm -300 μm ) to investigate the relaxation effect of electrical field stimulation (EFS, 10 Hz) assessed in the presence of guanethidine (adrenergic blocker, 5 μm ) and atropine (muscarinic cholinergic blocker, 1 μm ) to obtain non-adrenergic non-cholinergic (NANC) response. Cumulative administration of nicotine significantly potentiated the EFS-induced NANC relaxation (-log EC50 = 7.5 ± 0.057). Whereas, the potentiated NANC relaxation of nicotine was significantly inhibited with different concentrations of methyllycaconitine citrate (α7-nAChR antagonist, P < 0.05) in preincubated strips. L-NAME (non-specific nitric oxide synthase inhibitor, 1 μm ) completely blocked the neurogenic relaxation induced by EFS plus nicotine. Conclusion: To conclude α7-nAChR is expressed in rat CC and modulates the neurogenic relaxation response to nicotine.